Comparative Evaluation of the Sniffing Position with Simple Head Extension for Laryngoscopic View and Intubation Difficulty in Adults Undergoing Elective Surgery - Smita Prakash; Amy G. Rapsang; Saurabh Mahajan; Shameek Bhattacharjee; Rajvir Singh; Anoop R. Gogia (Anesthesiology Research and Practice)
The effect of patient position on mask ventilation, laryngoscopic view, intubation difficulty, and the stance adopted by the anesthesiologist during laryngoscopy and tracheal intubation was investigated in 546 anesthetized adults in this prospective, randomized study. Patients were randomly assigned to either the sniffing position group or the simple extension group. The distribution of Cormack grades was comparable between the two groups (P=0.144). The IDS score [median (IQR)] was 0 (0–2) in the sniffing group and 1 (0–2) in the simple extension group; P=0.002. There were significant differences between groups with regard to intensity of lifting force, external laryngeal manipulation, alternate techniques used, number of attempts, and the stance adopted by anesthesiologist. We conclude that the sniffing position is superior to simple head extension with regard to ease of intubation as assessed by IDS. An upright stance is adopted by more anesthesiologists performing intubation with patients in the sniffing position.